2021
DOI: 10.1007/s00248-021-01929-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable Keystone Bacteria Maintain the Functional Diversity of the Ixodes scapularis Microbiome Under Heat Stress

Abstract: Variations in the composition and diversity of tick microbiome due to high temperatures may influence the hierarchy of community members as a response to environmental change. Modifications in the community structure are hypothesized to drive alterations in the presence and/or abundance of functional pathways in the bacterial metagenome. In this study, this hypothesis was tested by using published 16S rRNA datasets of Ixodes scapularis males incubated at different temperatures (i.e., 4, 20, 30, and 37 °C) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Keystone taxa are known to have a major influence on the structure and function of microbiota at specific spatial or temporal contexts (Banerjee et al, 2018; Wu‐Chuang, Obregon, Mateos‐Hernández, et al, 2022). Certain keystone bacteria have been associated with the recovery of human gut microbiota after antibiotic exposure (Gibbons, 2020), and in another study, four keystone bacteria were found to maintain the functional diversity of the I. scapularis microbiota under intense heat stress (Wu‐Chuang et al, 2021; Wu‐Chuang, Obregon, Estrada‐Peña, et al, 2022). Through the privileged connectivity to keystone taxa in H. marginatum bacterial microbiota, Rickettsia may exert an influence microbial community assembly and resiliency to attack (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Keystone taxa are known to have a major influence on the structure and function of microbiota at specific spatial or temporal contexts (Banerjee et al, 2018; Wu‐Chuang, Obregon, Mateos‐Hernández, et al, 2022). Certain keystone bacteria have been associated with the recovery of human gut microbiota after antibiotic exposure (Gibbons, 2020), and in another study, four keystone bacteria were found to maintain the functional diversity of the I. scapularis microbiota under intense heat stress (Wu‐Chuang et al, 2021; Wu‐Chuang, Obregon, Estrada‐Peña, et al, 2022). Through the privileged connectivity to keystone taxa in H. marginatum bacterial microbiota, Rickettsia may exert an influence microbial community assembly and resiliency to attack (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Ticks have intricate ecological interactions with microorganisms present in their microbiota (Wu‐Chuang et al, 2021; Wu‐Chuang, Obregon, Estrada‐Peña, et al, 2022). Some of these microorganisms are considered human pathogens, such as Rickettsia sibirica mongolitimonae (Jakimovski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the microbiome of I. scapularis larvae and nymphs shared 80 taxa (24.6%, total 324), while out of 342 predicted metabolic pathways, 82.7%, were shared by all the tick samples ( Estrada-Peña et al, 2020a ). Furthermore, the I. scapularis microbiota exposed to pathogen infection, antimicrobial peptide or anti-tick host immunity shared a very reduced taxonomic core of 61 bacterial genera (7.4%, total 821), while the majority (i.e., 381) of the metabolic pathways (87.2%, total 437) were identified in all the samples ( Estrada-Peña et al, 2020b ), Also, despite high temperature altered the structure of the microbial community in I. scapularis ( Thapa et al, 2019 ; Wu-Chuang et al, 2021b ) four keystone taxa found across the temperature gradient, and their directly connected neighbors, contributed to more than 99% of the predicted pathways regardless the incubation temperature ( Wu-Chuang et al, 2021b ). This suggests that the tick microbiome is a stable source of metabolic functions with potential implications for tick physiology.…”
Section: The Symbiotic Continuum In Ticksmentioning
confidence: 99%